1970
DOI: 10.1111/j.1365-2621.1970.tb12137.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dry and Moist Heat Treatments on Selected Beef Quality Factors

Abstract: Pieces of beef semimembranosus muscle, relatively uniform in weight and shape, were deep-fat fried /OF/, oven-roasted (OR), oven-braised (OS) and pressure-braised (PBI at 1Opsig to an internal temperature of 70°C to investigate he effects of dry and moist heat on selected characteristics of beef. Rate of heat penetration, cooking time, cooking losses, total moisture, press fluid, water-holding capacity and juiciness varied lP < 0.01) and apparent degree of doneness varied lP < 0.05) among the 4 heat treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1972
1972
1996
1996

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It is known that the rate of heat penetration of meat depends on energy rate; transmission rate; size and shape of sample; composition and distribution of lean, fat, connective tissue, and bone (Paul and Palmer, 1972, p. 425). Research on cooking meat covered and uncovered showed that steam conducts heat more rapidly than air (Harrison, 1943;Schock, Harrison, and Anderson, 1970). Changes in meat are caused by heating and melting of fat, and protein denaturation and coagulation which lessens the water-holding capacity of the tissue.…”
Section: Diane Ferger Ruyack and Pauline C Paulmentioning
confidence: 99%
“…It is known that the rate of heat penetration of meat depends on energy rate; transmission rate; size and shape of sample; composition and distribution of lean, fat, connective tissue, and bone (Paul and Palmer, 1972, p. 425). Research on cooking meat covered and uncovered showed that steam conducts heat more rapidly than air (Harrison, 1943;Schock, Harrison, and Anderson, 1970). Changes in meat are caused by heating and melting of fat, and protein denaturation and coagulation which lessens the water-holding capacity of the tissue.…”
Section: Diane Ferger Ruyack and Pauline C Paulmentioning
confidence: 99%
“…Roasts cooked in a moist environment cooked more rapidly and had a lower cooked pH value (P<O.O5) than roasts cooked in the dry environment (Table 2). Meat reaches a specific internal temperature faster in a moist environment than in dry air (Schock et al 1970;Ferger et al 1972). Buck ef al.…”
Section: Resultsmentioning
confidence: 99%
“…In a moist cookery environment, the external surface will not exceed lOOC, whereas in a dry environment, the external surface may well exceed 1OOC. Cooking environment (moist versus dry) has been shown to alter cooking times, palatability, yields and moisture content of intact muscle roasts (Schock et al 1970;Ferger et al 1972;Buck et af. 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Cook yield and expressible moisture were higher at 70°C than at 100°C (Table 1). Others have found that higher cooking temperatures resulted in lower cook yield (Taki, 1965;Schock et al, 1970;Laakkonen, 1973).…”
Section: Resultsmentioning
confidence: 99%